Life history influences how fire affects genetic diversity in two lizard species. Issue 10 (5th May 2014) - Smith, Annabel L.; Bull, C. Michael; Gardner, Michael G.; Driscoll, Don A.
Abstract 'Fire mosaics' are often maintained in landscapes to promote successional diversity in vegetation with little understanding of how this will affect ecological processes in animal populations such as dispersal, social organization and re‐establishment. To investigate these processes, we conducted a replicated, spatiotemporal landscape genetics study of two Australian woodland lizard species [Amphibolurus norrisi (Agamidae) and Ctenotus atlas (Scincidae)]. Agamids have a more complex social and territory structure than skinks, so fire might have a greater impact on their population structure and thus genetic diversity. Genetic diversity increased with time since fire in C. atlas and decreased with time since fire in A. norrisi. For C. atlas, this might reflect its increasing population size after fire, but we could not detect increased gene flow that would reduce the loss of genetic diversity through genetic drift. Using landscape resistance analyses, we found no evidence that postfire habitat succession or topography affected gene flow in either species and we were unable to distinguish between survival and immigration as modes of postfire re‐establishment. In A. norrisi, we detected female‐biased dispersal, likely reflecting its territorial social structure and polygynous mating system. The increased genetic diversity in A. norrisi in recently burnt habitat might reflect a temporary disruption of its territoriality and increased male dispersal, a hypothesis that was supported with a simulation experiment. Our results suggest that the effects of disturbance on genetic diversity will be stronger for species with territorial social organization.